Rain anttenuation prediction model using radar data in Malaysia - Muhamad Haziq bin Khairolanuar (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
The nations in the tropical regions today are undergoing a rapid expansion in satellite communications with the increase in demand for long distance telecommunications, broadcastings and data channel requests. Due to rapidly increasing demand for more bandwidth, the radio frequencies used by the current satellite communication systems in these regions have been gradually shifted toward higher bands. At frequency bands above 10 GHz, rainfall is a serious cause of attenuation for radio-wave signal as the raindrops absorb and scatter its energy. Many researchers have put extensive efforts to measure and model the rain attenuation along the wireless propagation path. Measured data are typically applicable only to a specific location. This has caused a great challenge for researchers in their attempt to exploit the information to be used at other areas. For this reason, a “universal” prediction models are required by satellite designers to predict the likely rain attenuation. Current rain attenuation prediction models are incompatible to tropical climate, Malaysia included, as most of the models were developed in temperate region countries. The aim of the research is to develop an improved version of rain attenuation prediction model. In this research, one year of Malaysian Meteorological Department (MMD) radar and rain gauge data were analyzed. Another sets of data from Measat Broadcast Network System Sdn Bhd (MBSN) were examined as well. Radar and rain gauge data from MMD were used to analyze the vertical profile of rain. Radiometric and rain gauge data from MBSN were used as reference for comparison purpose. The model emulates the latest ITU-R P.618-12 currently in-force that requires information pertaining to rain height and rainfall rate at specific time percentage. The improved model can be achieved by exploiting the experimentally derived rain height information using radar data. The derivation of rain height information encompassed different value of top of melting layer height with respect to the rainfall rate value. From the analysis of the data, a new relationship of melting layer height with respect to rainfall rate is deduced. The new relationship was further used in developing the improved version of rain attenuation prediction model. The new model encompasses new process and calculation of estimated rain fade value. The new model was put into test with measured result and other previously proposed rain attenuation models namely ITU-R P.618-12 Rain Attenuation Prediction Model, Nallingam et al Model, Mandeep et al Model, Abdulrahman et al Model, Yussuf and Khamis Model and Ali et al Model. Based on comparison, the newly improved rain attenuation prediction model shows better correlation with 7.4% percentage error at 99.97% availability of time compared to measured result. The new model shows 33.5% improvement compared to the based model and 14.9% improvement compared to the closed models.